The Diversity of Ants (Hymenoptera: Formicidae) on Industrial Forest in Sungai Merah Village, Sarolangun, Jambi with Its Identification Key - Fitriyani, Nur Laras; Soesilohadi, RC. Hidayat; Purwanto, Hari (Universitas Gadjah Mada, 2024)
Ants have a very important role in an ecosystem. The insects act as decomposers, pollinators, soil aerators, pest controllers, and predators. Their role is very varied so that they can be easily found in various ecosystems, one of which is the rubber and oil palm ecosystem. The ant’s diversity in this forest eventually will affect the productivity of the land. The aim of this study is to determine the diversity and role of ants in the rubber and oil palm plantations in Sungai Merah Village. Both of the plantations dominate the industrial forest in Jambi. The method used in this study was purposive random sampling. Observation plots were installed in the ecosystem of rubber and oil palm plantations; each ecosystem had 4 plots consisting of 9 units of pitfall traps, and 9 units of bait traps. The results of this study show that 15 species of ants are found in the ecosystem of rubber and oil palm plantations. Furthermore, the collected ants consisted of 39.972 individual ants belonging to 12 genera and 5 subfamilies. Ants establish in the ecosystem of rubber and oil palm plantations in Sungai Merah Village have an important role either as predators (Crematogaster spp., Odontomachus rixosus, Odontoponera tranversa, Pheidole huberi, Tetraponera rufonigra, Tapinoma melanocephalum, Camponotus spp. and Colobopsis moeschi), or foragers such as ants from the genera Anoplolepis, Camponotus, Monomorium and Polyrhachis. As predators, Oecophylla smaragdina, Camponotus spp. and Crematogaster spp. also play a role as biological control agents in the ecosystem.